Video Dokumenter Informasi Kesenian Sisingaan Pada Dinas Pendidikan dan Kebudayaan Kabupaten Subang - M. Ifran Sanni; Alifya Nurcahya; Taufiq Kurniawan (UNIVERSITAS RAHARJA, 2021)
In the field of information, audio visual is one of the supporting media in delivering effective information, and is more attractive in its presentation. One of them is sisingaan art from Subang Regency, West Java. Currently, the art of sisingaan requires the design of media in the form of audio-visual because in presenting information on the existing side arts, there is no latest information on the latest side arts. The purpose of this study is to design audio-visual based media so that it can be useful and become an attraction for the community and art craftsmen regarding matters related to the arts of Subang district and increasing the number of sisingaan uses every year. The research methodology carried out during this research is problem analysis method, data collection method, design analysis method and media production concept method which includes preproduction, production and postproduction. After analyzing the above problems, the researchers designed a video for the Sisingaan art information of Subang Regency which is used to provide historical information and a very important lion shape icon. From the design of the art information video, it is hoped that the public will know more about the historical value and the lion symbol icon in the secondary arts of Subang Regency which cannot be removed or replaced with anything.